Association between plasma nonesterified fatty acids species and adipose tissue fatty acid composition. - Christian Hellmuth; Hans Demmelmair; Isabel Schmitt; Wolfgang Peissner; Matthias Blüher; Berthold Koletzko (PLoS ONE, 2013)
Fatty acid composition of adipose tissue (AT) is an established long-term biomarker for fatty acid (FA) intake and status, but AT samples are not easily available. Nonesterified FA composition in plasma (pNEFA) may be a good indicator of AT FA composition, because pNEFA are mainly generated by AT lipolysis. We investigated the correlation of 42 pNEFA and subcutaneous as well as visceral AT FA in 27 non-diabetic women with a median BMI of 36 kg/m(2) (Q0.25: 25 kg/m(2); Q0.75: 49 kg/m(2)). Close correlations of pNEFA and AT FA were found for odd-chain FA (15∶0 r = 0.838 and 0.862 for subcutaneous and visceral AT, respectively) and omega-3 FA (22∶6 r = 0.719/0.535), while no significant or low correlations were found for other FA including 18∶1 (r = 0.384/0.325) and 20∶4 (r = 0.386/0.266). Close correlations of pNEFA and AT FA were found for essential fatty acids, like 18∶2 (r = 0.541/0.610) and 20∶5 (r = 0.561/0.543). The lower correlation for some pNEFA species with AT FA indicates that the variation of most pNEFA is significantly affected by other FA sources and flux of FA to tissue, in addition to release from AT. A relevant influence of BMI on the level of correlation was shown for saturated FA. NEFA analysis in fasted plasma can serve as a virtual AT biopsy for some FA, and as a biomarker for intake of dairy products and sea fish.